Access of the substrate to the active site of squalene and oxidosqualene cyclases: comparative inhibition, site-directed mutagenesis and homology-modelling studies. (26th October 2005) - Oliaro-Bosso, S.; Schulz-Gasch, T.; Taramino, S.; Scaldaferri, M.; Viola, F.; Balliano, G.
Abstract : Substrate access to the active-site cavity of squalene-hopene cyclase from Alicyclobacillus acidocaldarious and lanosterol synthase [OSC (oxidosqualene cyclase)] from Saccharomyces cerevisiae was studied by an inhibition, mutagenesis and homology-modelling approach. Crystal structure and homology modelling indicate that both enzymes possess a narrow constriction that separates an entrance lipophilic channel from the active-site cavity. The role of the constriction as a mobile gate that permits substrate passage was investigated by experiments in which critically located Cys residues, either present in native protein or inserted by site-directed mutagenesis, were labelled with specifically designed thiol-reacting molecules. Some amino acid residues of the yeast enzyme, selected on the basis of sequence alignment and a homology model, were individually replaced by residues bearing side chains of different lengths, charges or hydrophobicities. In some of these mutants, substitution severely reduced enzymatic activity and thermal stability. Homology modelling revealed that in these mutants some critical stabilizing interactions could no longer occur. The possible critical role of entrance channel and constriction in specific substrate recognition by eukaryotic OSC is discussed.